Baseline living‐donor kidney volume and function associate with 1‐year post‐nephrectomy kidney function. Issue 3 (12th February 2019) - Hall, Isaac E.; Shaaban, Akram; Wei, Guo; Sikora, Magdalena B.; Bourija, Hassan; Beddhu, Srinivasan; Shihab, Fuad
Abstract: Living donors may develop kidney dysfunction more often than equally healthy populations. The purpose of this study was to determine whether computed tomography‐assessed remaining kidney volume indexed to body surface area (RKV/BSA) was associated with 1‐year post‐nephrectomy renal function independent of baseline renal function. Using multivariable regression, we modeled 1‐year estimated glomerular filtration rate (eGFR) and eGFR <60 mL /min/1.73 m 2 and considered pre‐determined baseline eGFR subgroups in 151 consecutive donors. Mean ± SD baseline age, eGFR, RKV, BSA, and RKV/BSA were 38 ± 11 years, 97 ± 16 mL/min/1.73 m 2, 153 ± 29 mL, 1.9 ± 0.2 m 2, and 80.0 ± 12.8 ml/m 2, respectively; 50% were female and 94% were white. Mean baseline eGFR was greater with increasing RKV/BSA tertiles (92 ± 14, 97 ± 16, 107 ± 16 mL/min/1.73 m 2 ; P  < 0.001). Post‐nephrectomy eGFR remained separated by RKV/BSA tertiles. At baseline, each SD greater RKV/BSA and eGFR was independently associated with higher adjusted 1‐year eGFR by 2.4 and 9.2 mL/min/1.73 m 2 . Each SD greater age associated with 2.2 mL/min/1.73 m 2 lower adjusted 1‐year eGFR. Adjusted odds of 1‐year eGFR <60 increased significantly for donors with RKV/BSA <80 mL/m 2 . With baseline eGFR <90, probability of 1‐year eGFR <60 increased to >80% with decreasing RKV/BSA values below 80 mL/m 2 . Those with baseline eGFR >100 rarely developed 1‐year eGFR <60 if RKV/BSA remained >60 mL/m 2 . RKV/BSA independently associated with 1‐year eGFR <60, especially with lower baseline eGFRs. Additional studies should evaluate the predictive utility of this measure and its potential role in donor evaluations and informed consent.